Behavioural, Sedative and Anticonvulsant Activities of Ethanol Extract of the Leaf of Lagenaria breviflora (Benth) in Mice (Nigerian Journal of Pharmaceutical Research, 2023)
Background: Lagenaria breviflora Benth is used in West Africa as a traditional remedy for the treatment of gastrointestinal disorders, the treatment of human measles, digestive disorders, and as a wound antiseptic.Objectives: This study investigated the behavioural, sedative, and anticonvulsant activities of the ethanol extract of Lagenaria breviflora (EOLB) in mice, and its possible mechanism(s) of action.Materials and Methods: The CNS activities of EOLB (100, 200, and 400 mg/kg, i.p., n=6) were evaluated using animal models of novelty-induced behaviours (NIB), sedation (ketamine-induced hypnosis), and anticonvulsion (maximal electroshock (MES)), pentylenetetrazole (PTZ), and strychnine). Probable mechanism(s) were evaluated using an antagonist (flumazenil, 2 mg/ml, i.p.) and an agonist (amphetamine (2 mg/kg, i.p.) on NIB.Results: LD50 values obtained were 1225 mg/kg and greater than 5000 mg/kg for the intraperitoneal and oral routes respectively. The EOLB at all doses tested significantly (p